The Impact of Family Employment on The Development of Algerian Small and Medium Enterprises - MERZOUGUI , Merzougui; GHANIA , Nadir (Journal of Finance & Corporate Governance, 2018)
Small and medium enterprises depend on the intensity of hand working, which shows the importance of human resources in them, but they still suffer from mis marketing of the human resource because of the family dominance over the management, which prefers the family member's employments. In this study we will try to measure its impact on the progress of Small and medium enterprises activity in Algeria